Navigational risk assessment of ships - Paulauskas, Vytautas (Transport, 2006)
This paper describes new methodology of creating the criteria for assessing navigational risk. Various factors influencing the navigational risk assessment are described. The method of calculating and evaluating ship risk probability is presented in this paper. Practical methods of ship navigational risk probability and assessment with the explanation for particular regions are described. The paper concludes with identifying sea regions with more risk based on a large number of factors.First Published Online: 27 Oct 2010